A Tale of Competition between Eastern and Southern Europe (Rerum Concordia Discors) - Peter Egger; Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2001)
This paper assesses the relationship between EU manufacturing imports from the southern EU and the CEEC. Final goods imports are strongly complementary and intermediate goods imports are substitutive. An increase in the high-skilled to low-skilled labor ratio in the EU-South or the degree of intra-EU multinationality lowers competition in intermediate goods trade between the EU-South and the CEEC.
Keywords: F14; F15; 330; Economic integration; Eastern enlargement; Außenhandel mit Industriegütern; EU-Binnenhandel; Internationaler Wettbewerb; Nachfragesystem; Schätzung; Südeuropa; Osteuropa